Prevalence of Hepatitis B Co-Infection among HIV Positive Patients: Narrative Review Article. - Azam Askari; Hamid Hakimi; Behzad Nasiri Ahmadabadi; Gholamhossein Hassanshahi; Mohammad Kazemi Arababadi (Tehran University of Medical Sciences, 2014)
Hepatitis B virus (HBV) is the most prevalent viral infection and is among the leading causes of human liver diseases. Nearly 360 millions of people are world widely infected with prolonged forms of hepatitis B including active and inactive chronic forms. Chronic hepatitis B (CHB) is associated with cirrhosis and hepatocellular carcinoma (HCC) in patients suffering from congenital and/or acquired immunodeficiency and also following immunosuppressive therapy. The target cell of human acquired immunodeficiency virus (HIV) is CD4 positive T cells. These cells play central role(s) in both cellular and humoral immunity so that the HIV attack of CD4 positive T cells causes suppression of both cell-mediated and humoral immune responses. One of the frequent complications in HIV positive patients is HBV co-infection and as a result, the co-transmission of these viral diseases is common. Due to the paramount importance of the co-infection of HBV and HIV, it is noteworthy to investigate the prevalence of hepatitis B in these patients for planning of an effective therapeutic strategy. Based on these considerations, the main aim of this review article was to collect and analyze the recent and relevant studies regarding the prevalence rate of hepatitis B co-infection among HIV positive patients world widely.